2017
DOI: 10.1007/s00726-017-2508-0
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and glycine metabolism in humans

Abstract: Plasma glycine level is low in patients with obesity or diabetes and the improvement of insulin resistance increases plasma glycine concentration. In prospective studies, hypoglycinemia at baseline predicts the risk of developing type 2 diabetes and higher serum glycine level is associated with decreased risk of incident type 2 diabetes. Consistently, plasma glycine concentration is lower in the lean offspring of parents with type 2 diabetes compared to healthy subjects. Among patients with type 2 diabetes, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 94 publications
6
95
0
Order By: Relevance
“…The reaction catalyzed by SHMT1 is an important source of glycine [14,15] and hypoglycinemia was shown to contribute to occurrence of vascular calcification and elevated cardiovascular risk in diabetes and CKD [47]. Furthermore, direct targets of SHMT1-mediated methylation [18][19][20][21] may be involved in osteoinductive signaling in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction catalyzed by SHMT1 is an important source of glycine [14,15] and hypoglycinemia was shown to contribute to occurrence of vascular calcification and elevated cardiovascular risk in diabetes and CKD [47]. Furthermore, direct targets of SHMT1-mediated methylation [18][19][20][21] may be involved in osteoinductive signaling in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 Previous studies indicated that plasma glycine level is a negative biomarker in patients with diabetes mellitus. [18][19][20][21] Glycine metabolism pathway indicates the participation of many other important metabolites that mostly serve in the biosynthesis of glycine. However, many of these metabolites have not been proven to be associated with insulin resistance or diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…28 In addition, the reduced plasma betaine level was also found to act as a positive biomarker of diabetes mellitus and proved to be associated with incident T2D. 16,21 Bile acid (BA) metabolism was reported to be involved in cholesterol as well as glucose metabolism homeostasis. 29 The latter authors claimed that insulin resistance is positively associated with hyperbileacidemia regardless of diabetes status, which indicates the important role of insulin resistance in the regulation of "bile secretion" pathway in human.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the significant heterogeneity of association results between sexes for CSF p-tau and glycine, with higher levels of glycine being linked to higher levels of CSF p-tau in men, indicates that energy demands are equally upregulated in males as in females. In contrast to women, men, however, appear to compensate this demand by upregulation of glucose energy metabolism as glycine is a positive marker of active glucose metabolism and insulin sensitivity (67). Findings for acylcarnitines in females are further contrasted by the observed male-specific association of higher levels of the long-chain acylcarnitine C16:1 with decreased brain glucose uptake, which might indicate that in males there is a switch to provision of fatty acids as alternative fuel when glucose-based energy metabolism is less effective.…”
Section: Metabolic Effect Heterogeneity Suggests Sex-specific Differementioning
confidence: 94%